Financial Crisis and Health - Maria Saridi (Global Journal of Cancer Therapy - Peertechz Publications, 2015)
The financial crisis has a dramatic impact on social life, since reduced or even non-existent incomes affect people's well-being and push big parts of the population to poverty. The individuals' financial status affects health indicators such as life expectancy, morbidity, mortality and healthcare service accessibility [1]. The negative impact of financial crisis on health affects in a different way the social groups; thus, low-level persons and families have twice the risk of premature death and higher morbidity due to reasons related to income, education, healthcare, housing and nutrition that act cumulatively [2].  This situation poses a threat mainly for the least developed and developing countries, and even more the low-level social groups within those countries, and highlights three intertwined problems: (a) increasing inequalities within those countries, (b) unequal conditions of social protection and health, and (c) the urgent issues of climate change and environmental degradation [3].